Fractal Analysis in Pulmonary CT Images of COVID-19-Infected Patients - Maria-Alexandra Paun; Paraschiva Postolache; Mihai-Virgil Nichita; Vladimir-Alexandru Paun; Viorel-Puiu Paun (Fractal and Fractional, 2023)
In this paper, we propose to quantitatively compare the loss of human lung health under the influence of the illness with COVID-19, based on the fractal-analysis interpretation of the chest-pulmonary CT pictures, in the case of small datasets, which are usually encountered in medical applications. The fractal analysis characteristics, such as fractal dimension and lacunarity measured values, have been utilized as an effective advisor to interpretation of pulmonary CT picture texture.